1990
DOI: 10.1002/ana.410270408
|View full text |Cite
|
Sign up to set email alerts
|

Infantile spasms: I. PET identifies focal cortical dysgenesis in cryptogenic cases for surgical treatment

Abstract: Positron emission tomography (PET) of local cerebral glucose metabolism in 13 children with infantile spasms of undetermined cause (cryptogenic spasms) revealed unilateral hypometabolism involving the parieto-occipito-temporal region in 5 female infants. Cranial computed tomography showed normal findings in all infants. Magnetic resonance imaging (MRI) demonstrated a normal appearance in 4 of the 5 infants; in 1 infant, MRI revealed a subtle abnormality consisting of poor demarcation between occipital gray and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
245
1
8

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 576 publications
(273 citation statements)
references
References 21 publications
(1 reference statement)
13
245
1
8
Order By: Relevance
“…According to this model, spasms would result from projections of the activated brainstem regions to the spinal cord neurons as well as from the lenticular activation. This model provides an explanation for the observation that patients with infantile spasms with lesions confined to the cerebral cortex can have their spasms abolished and their EEGs improved after resection of cortical lesions (Chugani et al, 1990, Uthman et al, 1991, Wyllie et al, 1996b, Hrachovy and Frost, 2003. It is still unclear, however, which structures in the described network are primarily responsible for hypsarrhythmia.…”
Section: Pathogenesismentioning
confidence: 89%
See 1 more Smart Citation
“…According to this model, spasms would result from projections of the activated brainstem regions to the spinal cord neurons as well as from the lenticular activation. This model provides an explanation for the observation that patients with infantile spasms with lesions confined to the cerebral cortex can have their spasms abolished and their EEGs improved after resection of cortical lesions (Chugani et al, 1990, Uthman et al, 1991, Wyllie et al, 1996b, Hrachovy and Frost, 2003. It is still unclear, however, which structures in the described network are primarily responsible for hypsarrhythmia.…”
Section: Pathogenesismentioning
confidence: 89%
“…Studies on functional neuroimaging mostly with PET technology in West syndrome have revealed putamen, brainstem and various cortical regions playing an important role in the pathogenesis of hypsarrhythmia (Chugani et al, 1990, Haginoya et al, 2000, Hrachovy et al, 1981, Morimatsu et al, 1972, Metsahonkala et al, 2002, Neville, 1972, Satoh et al, 1986, Hrachovy and Frost, 2003. Using simultaneous EEG-fMRI recordings, Siniatchkin et al (2007) have demonstrated recently, that the high-amplitude slow cortical activity in hypsarrhythmia is associated with positive BOLD effects in putamen and brainstem, and that multifocal epileptiform discharges are correlated with positive BOLD effects in occipital cortex and various other cortical areas.…”
Section: Pathogenesismentioning
confidence: 99%
“…Moreover, infantile spasms have been suppressed by surgical removal of focal cortical lesions where focal hypometabolism was detected by positron emission tomography (15). Regarding the relation between cortical and sub- gested that the cortical epileptogenic region involving the primary sensorimotor area could function as the primary generator for infantile spasms because focal pathologic lesions were detected in those areas by MRI and positron-emission tomography (PET) scans, and asymmetric and asynchronous spasms were significantly associated with contralateral ictal EEG discharges.…”
Section: Discussionmentioning
confidence: 99%
“…For these refractory cases, therapy with novel AEDs are definitely necessary (14) especially in Japan, since many AEDs used in other countries have never been available in Japan. Alternatively, some of these cases can be successfully treated by epilepsy surgery, especially cases in Group PE (15,16). We must search extensively for candidates for epilepsy surgery as early in the patients' lives as possible The other group that comprises patients with rare seizures and those in remission but still on AEDs has received insufficient attention to date because of a lack of long-term follow-up studies throughout their lives (13).…”
Section: Discussionmentioning
confidence: 99%